The nature of the Fe–graphene interface at the nanometer level1. Issue 6 (14th February 2015) - Cattelan, M.; Peng, G. W.; Cavaliere, E.; Artiglia, L.; Barinov, A.; Roling, L. T.; Favaro, M.; Píš, I.; Nappini, S.; Magnano, E.; Bondino, F.; Gavioli, L.; et al.
<x xml:space="preserve">Abstract</x> The interaction of iron with graphene/Pt(111) has been experimentally and theoretically investigated evidencing a splitting of graphene π bands due to the hybridization with Fe 3d states.